Research on the influencing factors of the development of metabolic syndrome in patients with schizophrenia and the intervention effect of dance movement therapy - Wang, Suhong; Zhou, Yue; Zhu, Xueli; Yu, Yangyang; Xiao, Weixia; Sun, Qianqian; Yan, Fang; Wang, Chuansheng (Frontiers in Psychiatry, 2025)
ObjectivesPatients with schizophrenia are at increased risk for metabolic syndrome (MS), which can lead to cardiovascular diseases and diabetes, potentially worsening mental symptoms and hindering recovery. Dance movement therapy (DMT), a non-pharmacological intervention that combined movement with psychological regulation, may improve mood and cognition. This study aimed to investigate factors influencing MS in schizophrenia and evaluate the intervention effect of DMT.MethodsA total of 160 patients with schizophrenia who were admitted to our hospital from April 2021 to April 2023 were prospectively included. According to whether MS occurred, patients were allocated into the MS group (n=80) and the non-MS group (n=80). Logistic regression was used to analyze factors influencing MS. Subsequently, the MS group was randomly allocated to a control group (n=40), which received conventional treatment, and an intervention group (n=40), which received DMT in addition to conventional care. The metabolic indicators and positive and negative syndrome scale (PANSS) scores of both groups before and after the intervention were collected to evaluate the intervention effect of DMT.ResultsThe advanced age, smoking habit, high BMI and interleukin-6 (IL-6) levels, long medication time, and elevated CRP levels were risk factors for the development of MS. Moderate exercise habits were protective factors. After the DMT intervention, body mass index (BMI), waist circumference (WC), diastolic blood pressure (DBP), and PANSS scores of the intervention group showed a downward trend as the intervention time increased. However, the BMI, WC, DBP, and PANSS scores of the control group displayed an increasing tendency. In addition, the BMI, WC, DBP, fasting blood glucose (FBG), and PANSS scores of the intervention group were less than those of the control group 4 weeks and 8 weeks after the intervention.ConclusionAge, smoking habit, BMI and IL-6 levels, medication time, elevated CRP levels, and exercise habit were the influencing factors for the development of MS in schizophrenia. DMT could effectively improve metabolic parameters and psychiatric symptoms in these patients. However, the study has limitations such as a short intervention period and a single-center design. Future research should verify this results through multi-center studies and longer follow-up periods.